Oncology service initiatives and research in regional Australia. (February 2015) - Murphy, Caitlin; Sabesan, Sabe; Steer, Christopher; Yates, Patsy; Booms, Anne; Jones, Victoria; Simpson, Alison; Clarke, Kerrie; Eek, Richard; Ashley, David; Goldstein, David; Packer, Chris; et al.
Abstract Objective This paper reflects on the recent growth of cancer research being conducted through some of Australia's rural centres. It encompasses work being done across the fields of clinical, translational and health services research. Design This is a collaborative piece with contributions from rural health researchers, clinical and cancer services staff from several different regions. Conclusion The past decade has seen an expansion in cancer research in rural and regional Australia driven in part by the recognition that cancer patients in remote areas experience poorer outcomes than their metropolitan counterparts. This work has led to the development of more effective cancer networks and new models of care designed to meet the particular needs of the rural cancer patient. It is hoped that the growth of cancer research in regional centres will, in time, reduce the disparity between rural and urban communities and improve outcomes for cancer patients across both populations.